State, society and national security challenges and opportunities in the 21st century - Jayakumar, Shashi (World Scientific, 2016)
Addressing the complexities of radicalisation, resilience, cyber, and homeland security, State, Society and National Security: Challenges and Opportunities in the 21st Century aims to shed light on what has changed in recent years security discourse, what has worked (as well as what has not), and what the potential further evolutions within each domain might be.